Using hawgent dynamic mathematics software in teaching arithmetic operation - Suan Lin; Ying Zhou; Tommy Tanu Wijaya (International Journal of Education and Learning, 2020)
Dynamic learning software is an auxiliary tool to help students understand the mathematical operation process. Sometimes the calculation methods of textbooks are dull and boring, an innovative teaching medium is needed to assist teaching. This research aims to create a learning medium to improve students' ability to learn rational arithmetic. The learning process will use hawgent dynamic mathematics software as the mathematics learning medium. This research designed in conjunction with the four steps of solving problems in Polya. This study involved 30 junior high school students as the research subject. The tools used in this study are cognitive tests, interviews and observations. The research results show that the use of hawgent dynamic mathematics software can improve the students' ability to operate rational numbers. This means that the realization of hawgent dynamic mathematics software in the process of mathematics learning is successful. Students are more active and enthusiastic in the classroom. In short, the development of hawgent dynamic mathematics software can improve students' rational number operation ability, because with the help of hawgent, students will increase their motivation to learn.